2003
DOI: 10.1007/s00246-002-0216-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Failure and Retreatment in Kawasaki Disease

Abstract: Several cases of Kawasaki disease (KD) were unresponsive to the initial treatment with intravenous immunoglobulin (IVIG). We retrospectively analyzed all children admitted with KD to determine the occurrence and variables associated with the initial IVIG treatment failure. All patients who fulfilled the criteria for KD and were treated with a single dose (2 g/kg) of IVIG between January 1995 and August 2001 were enrolled. An analysis of the patients who had initially failed to respond to IVIG was performed. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
149
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(160 citation statements)
references
References 11 publications
6
149
0
5
Order By: Relevance
“…We found no difference in the incidence of rKD with regard to gender, age, or ethnicity. Some of these fi ndings are in accordance with results of studies by Do et al, 14 Cha et al, 15 and Durongpisitkul et al, 16 who have reported similar age and gender distribution between rKD and sKD in Korea and Thailand. Our results contrast with other studies that have found younger age to be a predictor for rKD.…”
Section: Discussionsupporting
confidence: 91%
“…We found no difference in the incidence of rKD with regard to gender, age, or ethnicity. Some of these fi ndings are in accordance with results of studies by Do et al, 14 Cha et al, 15 and Durongpisitkul et al, 16 who have reported similar age and gender distribution between rKD and sKD in Korea and Thailand. Our results contrast with other studies that have found younger age to be a predictor for rKD.…”
Section: Discussionsupporting
confidence: 91%
“…Multiple scoring systems for predicting IVIG-resistance in patients with KD have been published from other countries (2,(12)(13)(14). However, the only scoring system for which we had all of the variables in our database was published by Egami et al from Japan (12).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with a single dose of intravenous immunoglobulin (IVIG) and high-dose aspirin results in resolution of fever in most patients and significantly reduces the rate of coronary artery aneurysms (1). Despite this success, 10-20% of children will have persistent or recrudescent fever after their first infusion of IVIG (2)(3)(4)(5). These patients are at increased risk of developing coronary artery abnormalities (5,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…156,167,168 Failure to respond usually is defined as persistent or recrudescent fever Ն36 hours after completion of the initial IVIG infusion. Most experts recommend retreatment with IVIG, 2 g/kg (evidence level C).…”
Section: Ivigmentioning
confidence: 99%